2002
DOI: 10.1080/019262302753559551
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Cystic Degeneration/Spongiosis Hepatis in Rats

Abstract: Cystic degeneration /spongiosis hepatis in rats has been proposed to be a preneoplastic and/or neoplastic lesion by some authors, because of its proliferative properties and persistent increased cell turnover rate in stop experiments using hepatocarcinogens , and the assumption that it can develop into a sarcoma. The neoplastic potential of cystic degeneration is questioned in this review article. Cystic degeneration , which appears to derive from altered Ito cells, does not have neoplastic histomorphologi c c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
(118 reference statements)
1
14
0
Order By: Relevance
“…One group has proposed that spongiosis hepatis may be a preneoplastic and/or neoplastic lesion because of its proliferative properties and persistent increased cell turnover rate in stop experiments with hepatocarcinogens, and the assumption that it can develop into a sarcoma 26 . In contrast, the other group has suggested that the lesion may be a secondary/ reparative change but not a preneoplastic or neoplastic lesion, because spongiosis hepatis was more associated with hepatocellular h y p e r t r o p h y o r h e p a t o t o x i c i t y , r a t h e r t h a n hepatocarcinogenicity in 12 oncogenicity studies in rats with induced spongiosis hepatis 27 . In addition, the group has indicated that persistent proliferation is also seen with other nonneoplastic lesions and spongiosis hepatis does not have neoplastic histomorphologic characteristics.…”
Section: Spongiosis Hepatismentioning
confidence: 92%
“…One group has proposed that spongiosis hepatis may be a preneoplastic and/or neoplastic lesion because of its proliferative properties and persistent increased cell turnover rate in stop experiments with hepatocarcinogens, and the assumption that it can develop into a sarcoma 26 . In contrast, the other group has suggested that the lesion may be a secondary/ reparative change but not a preneoplastic or neoplastic lesion, because spongiosis hepatis was more associated with hepatocellular h y p e r t r o p h y o r h e p a t o t o x i c i t y , r a t h e r t h a n hepatocarcinogenicity in 12 oncogenicity studies in rats with induced spongiosis hepatis 27 . In addition, the group has indicated that persistent proliferation is also seen with other nonneoplastic lesions and spongiosis hepatis does not have neoplastic histomorphologic characteristics.…”
Section: Spongiosis Hepatismentioning
confidence: 92%
“…Therefore, they concluded that spongiosis hepatis was not a consequence of MCL. Spongiosis hepatis may occur in association with hepatocarcinogens (e.g., Bannasch et al, 1981;Braunbeck et al, 1992;Zerban and Bannasch, 1983), but frequently occurs in the absence of hepatocarcinogenesis and peroxisome proliferation (reviewed in CPSC, 2002;Karbe and Kerlin, 2002). Spongiosis hepatis has not been reported in humans (Karbe and Kerlin, 2002).…”
Section: Acceptable Daily Intakementioning
confidence: 97%
“…Lipomatous lesions in the liver are thought to be tumors originating from Ito cells 1,5 . In addition, neoplasms derived from Ito cells associated with spongiosis hepatis have been previously described in rats 6,7 . Although the mechanism remains unclear, the vacuolated (lipid-laden) and spindle-shaped cells in the present study could be phenotypes of Ito cells as reported previously in rats 7 and mice 3 .…”
mentioning
confidence: 99%
“…In addition, neoplasms derived from Ito cells associated with spongiosis hepatis have been previously described in rats 6,7 . Although the mechanism remains unclear, the vacuolated (lipid-laden) and spindle-shaped cells in the present study could be phenotypes of Ito cells as reported previously in rats 7 and mice 3 . Immunohistochemical examination of the present case revealed that vimentin was partially expressed in some of the prolifelative cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation